Histological and MRI brain atlas of the common shrew, Sorex araneus, with brain region-specific gene expression profiles - Baldoni, Cecilia; Thomas, William R.; von Elverfeldt, Dominik; Reisert, Marco; Làzaro, Javier; Muturi, Marion; Dávalos, Liliana M.; Nieland, John D.; Dechmann, Dina K. N. (Frontiers in Neuroanatomy, 2023)
The common shrew, Sorex araneus, is a small mammal of growing interest in neuroscience research, as it exhibits dramatic and reversible seasonal changes in individual brain size and organization (a process known as Dehnel’s phenomenon). Despite decades of studies on this system, the mechanisms behind the structural changes during Dehnel’s phenomenon are not yet understood. To resolve these questions and foster research on this unique species, we present the first combined histological, magnetic resonance imaging (MRI), and transcriptomic atlas of the common shrew brain. Our integrated morphometric brain atlas provides easily obtainable and comparable anatomic structures, while transcriptomic mapping identified distinct expression profiles across most brain regions. These results suggest that high-resolution morphological and genetic research is pivotal for elucidating the mechanisms underlying Dehnel’s phenomenon while providing a communal resource for continued research on a model of natural mammalian regeneration. Morphometric and NCBI Sequencing Read Archive are available at https://doi.org/10.17617/3.HVW8ZN.